2021
DOI: 10.1123/jsr.2020-0276
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Immediate Effect of Petrissage Massage and Manual Lymph Drainage Following Exercise on Biomechanical and Viscoelastic Properties of the Rectus Femoris Muscle in Women

Abstract: Context: Fast and adequate recovery after exercise and activity is important for increasing performance and preventing injuries. Inadequate recovery usually causes changes in the biomechanical and viscoelastic properties of the muscle. Objective: To compare the immediate effect of petrissage massage (PM) and manual lymph drainage (MLD) following submaximal exercise on the biomechanical and viscoelastic properties of the rectus femoris muscle in healthy women. Design: Cross-sectional, repeated-measures. Setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Then, at the 5th and 10th min after front squats, the muscle mechanical property assessments were repeated. Those time points were selected since previous studies showed that changes in muscle mechanical properties last up to ~10 min following low-volume exercises [ 10 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, at the 5th and 10th min after front squats, the muscle mechanical property assessments were repeated. Those time points were selected since previous studies showed that changes in muscle mechanical properties last up to ~10 min following low-volume exercises [ 10 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Examining minor alterations in muscle stiffness and muscle oscillation frequency could be useful in detecting the initial onset of muscle fatigue. This approach has been highlighted in previous studies [10,16,18]. Fast and adequate recovery after exercise plays a crucial role in enhancing performance and reducing the risk of injuries [19].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The most frequently mentioned benefits of using PM include reducing pain and muscle spasms, increasing blood and lymphatic flow, increasing range of motion, and accelerating recovery [ 4 , 5 , 6 ]. Depending on the purpose, the PM is applied as a part of a warm-up, for instance, to increase the range of motion, or whether inter- and post-activity to accelerate recovery [ 4 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Massage therapy has the potential to benefit mental health and general well-being as it has been reported to alleviate stress and fatigue as well as promote sleep through relaxation and improving blood circulation, blood pressure [ 20 , 21 ] and support tissue recovery and aid in the prevention of injury after exercise [ 22 ]. Additional to the mental health and general well-being benefits of massage therapy, it has also been found to be effective in the treatment of musculoskeletal pain, arthritic and general back pain, neck pain and hip pain [ 18 , 21 ].…”
Section: Introductionmentioning
confidence: 99%